Cubus: autonomous embodied characters to stimulate creative idea generation in groups of children - Pires, A. (2018)
Creativity is an ability that is crucial in nowadays societies. It is, therefore, important to develop activities that stimulate creativity at a very young age. It seems, however, that there is a lack of tools to support these activities. In this paper, we introduce Cubus, a tool that uses autonomous synthetic characters to stimulate idea generation in groups of children during a storytelling activity. With Cubus, children can invent a story and use the stop-motion technique to record a movie depicting it. In this paper, we explain Cubus’ system design and architecture and present the evaluation of Cubus’ impact in a creative task. This evaluation investigated idea generation in groups of children during their creative process of storytelling. Results showed that the autonomous behaviors of Cubus’ virtual agents contributed to the generation of more ideas in children, a key dimension of creativity.